Touching tumour‐infiltrating lymphocytes in low‐risk ductal carcinoma in situ (DCIS) correlate with upgrading to high‐grade DCIS. Issue 2 (22nd September 2021) - Khoury, Thaer; Quinn, Marie; Tian, Wanqing; Yan, Li; Zhan, Haiying
Abstract : Aims: To examine our hypothesis that a higher number of touching tumour‐infiltrating lymphocytes (TILs) in low‐risk ductal carcinoma in situ (DCIS) detected in a setting such as an active surveillance clinical trial correlates with upgrading to high‐grade DCIS (HG‐DCIS) in the subsequent excisional biopsy. Methods and results: The clinical inclusion criteria of the Comparison of Operative versus Monitoring and Endocrine Therapy (COMET) trial were applied to women who were mammographically screened between 2007 and 2017. In the core needle biopsy, touching TILs were assessed by counting the number of TILs touching the ductal basement membrane or away from it by one lymphocyte thickness. The highest number of TILs around a single involved duct and the average number among involved ducts were recorded. DCIS was graded as low or intermediate. Twenty‐six of 129 (20.2%) cases had upgrading [14 (10.9%) to pure HG‐DCIS, and 12 (9.3%) to invasive carcinoma, two of them with concurrent HG‐DCIS]. An increased average number of touching TILs and intermediate‐grade DCIS correlated with upgrading to HG‐DCIS in 11 of 16 (68.8%) cases, and a decreased average number of touching TILs and low‐grade DCIS correlated with no upgrading in 89 of 113 (78.8%) cases [accuracy of 0.775; area under the curve (AUC) of 0.746]. An increased highest number of touching TILs and intermediate‐grade DCIS correlated with upgrading to HG‐DCIS in 12 of 16 (75%) cases, and a decreased highest number of touching TILs and low‐grade DCIS correlated with no upgrading in 82 of 113 (72.6%) cases (accuracy of 0.7287; AUC of 0.734). A highest number of touching TILs of ≥10 correlated with upgrading to invasive carcinoma and/or HG‐DCIS ( P  = 0.018). Conclusions: Intermediate‐grade and touching TILs may be good variables to examine in the COMET trial and to correlate with the risk of upgrading. Abstract :